2020
DOI: 10.3892/mmr.2020.10934
|View full text |Cite
|
Sign up to set email alerts
|

The peptide compound urantide regulates collagen metabolism in atherosclerotic rat hearts and inhibits the JAK2/STAT3 pathway

Abstract: The aim of the present study was to investigate the effect of urantide on collagen metabolism in the hearts of rats with atherosclerosis (aS) by evaluating the expression of Janus kinase 2 (JaK2)/signal transducer and activator of transcription 3 (STaT3) pathway constituents. urantide was delivered to rats with aS via tail vein injection for 3, 7 and 14 days. Serological indicators were identified by an automated biochemical analyzer. Histomorphological changes in the cardiac tissue of rats were observed by pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…At present, to the best of our knowledge, only the authors' research team has provided a small amount of evidence indicating that urantide blocks the effects of UII on promoting the occurrence and development of AS ( 10 , 11 ). Concurrently, as shown in our previous studies using an AS rat model, urantide exerted protective effects on myocardial collagen metabolism disorder ( 34 ) and kidney injury ( 35 ), and the survival rate of rats with AS was also greatly improved by injecting with 30 µg/kg urantide. As to whether human patients are suitable for this dose, it is necessary to determine the best dose for patients by converting the equivalent dose between animals and humans.…”
Section: Discussionsupporting
confidence: 60%
“…At present, to the best of our knowledge, only the authors' research team has provided a small amount of evidence indicating that urantide blocks the effects of UII on promoting the occurrence and development of AS ( 10 , 11 ). Concurrently, as shown in our previous studies using an AS rat model, urantide exerted protective effects on myocardial collagen metabolism disorder ( 34 ) and kidney injury ( 35 ), and the survival rate of rats with AS was also greatly improved by injecting with 30 µg/kg urantide. As to whether human patients are suitable for this dose, it is necessary to determine the best dose for patients by converting the equivalent dose between animals and humans.…”
Section: Discussionsupporting
confidence: 60%
“…The positive regulatory effect of METTL3 on JAK2 expression and JAK2/STAT3 pathway also has been identified by a prior study, which demonstrated that METTL3 knockdown inhibited cell self-renewal and induced cell differentiation by reducing JAK2 expression and inactivating the JAK2/STAT3 pathway in porcine induced pluripotent stem cells ( Wu et al, 2019 ). Moreover, JAK2/STAT3 signaling pathway has been found to be implicated in the pathogenesis of AS ( Wang et al, 2020c ; Wang et al, 2020d ). For example, the inhibition of JAK2/STAT3 signaling by JAK2 inhibitor Ruxolitinib inhibited AS progression, alleviated lipid and calcium burdens, and weakened proinflammatory responses in AS rabbits ( Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%